A Small Body Sized Non-Aristonectine Elasmosaurid (Sauropterygia, Plesiosauria) from the Late Cretaceous of Patagonia with Comments on the Relationships of the Patagonian and Antarctic Elasmosaurids - O'Gorman, José Patricio (2016)
The systematics of the Late Cretaceous non-aristonectine elasmosaurids from Argentinean Patagonia are poorly known as there is no valid species currently recognized. Here a new non-aristonectine elasmosaurid: Kawanectes lafquenianum nov. comb. from the late Campanian—early Maastrichtian Allen Formation is diagnosed. K. lafquenianum is a distinctively small-body sized non-aristonectine elasmosaurid characterized by caudal vertebrae with marked laterally projected parapophyses, presence of pelvic bar, high ratio (∼1.2) between humerus/femur length and a large posterodistal projection of the humerus which bears a posterior accessory articular facet. A phylogenetic analysis recovered K. lafquenianum closely related with Morenosaurus stocki, Vegasaurus molyi, and Aristonectinae, showing the relationships between the elasmosaurids from Patagonia, Western Antarctic, and the Pacific coast of the USA. K. lafquenianum is part of the fauna of the coeval Allen and La Colonia formations that also comprises indeterminate aristonectines and polycotylids. This relatively high diversity plesiosaur fauna includes the three main morphotypes (aristonectines, non-aristonectine elasmosaurids and polycotylids), which is remarkable because the depositational environments of the Allen Formation have been inferred as marginal marine to non-marine environments.